Kepatuhan dan Asertivitas Pegawai Negeri sipil (PNS) Pada Penerapan Peraturan Daerah Kawasan Tanap Rokok (KTR) " Studi Komparasi di Kabupaten Sleman dan Kabupaten Kulon Progo Tahun 2017" (Berita Kedokteran Masyarakat (BKM), 2018)
Purpose: The aim of this research is to determine the difference of compliance and assertiveness of civil servants on the application of no-smoking areas in Sleman and Kulon Progo districts. Method: This research is an analytic survey research with cross sectional approach. The subjects of the research are civil servants in the regional government unit of work (satuan kerja perangkat daerah) of Kulon Progo District as many as 1,072 employees and Sleman as many as 2,300 employees from 26 regional government unit of work in Sleman and 25 regional government unit of work in Kulon Progo. The sampling technique is multistage random sampling technique. The research instrument is measured by questionnaires, and also observations and interviews to support the research. The analysis used is independent t-test and Mann-Whitney, which are to test whether there is a relationship between independent and dependent variables. Results: Independent t-test and Mann-Whitney test results showed that there is a difference of knowledge on the implementation of regional regulation of no-smoking areas with (p=0,000), attitude with (p=0,003)  and difference of socialization on the implementation of regional regulation of no-smoking area with (p=0,000) Logistic regression test results shows that the dominant factor influencing the implementation of the regional regulation of no-smoking area is knowledge with p value=0,000. Conclusion: There is a difference of knowledge, attitude and socialization of civil servants in Kulon progo and Sleman districts. There is no difference in attitude, smoking status, compliance, assertiveness, accessibility and coworkers who smoke of civil servants in Kulon progo and Sleman districts. The dominant factor affecting the compliance and assertiveness of civil servants is knowledge.